Custom and Its Impact on Hanafi Jurisprudence and Applications in Contemporary Fatwas - Shariati, Nasir Ahmed; Haqyar, Fazul Rahman (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
Among the cosmic laws of Almighty Allah are the change of conditions, the alteration of circumstances and times, and the continuity of renewal. Every time has its own customs and characteristics, and what is unique to this time is scientific development and technological progress. We know that modern discoveries have an impact on changing some fatwas, there is no doubt that changing customs, times, and conditions have their impact on fatwas. In this research, we study the impact of changing customs on changing fatwas, as we witness a change in some contemporary fatwas from what they were in past times, which raises a question about the reasons for this change. This research answers this question with some scientific foundations, demonstrating contemporary jurisprudential applications that indicate the extent of the impact of changing customs on changing fatwas, and the impact of all of that on the movement. Jurisprudence, especially in recent times. In addition, custom in the custom of jurists, as Imam Al-Shafi’i said: (And custom is what people know and agree upon among themselves in dealings). Custom is a great need, especially in issues that have mentioned. In general and were not specified in Islamic law, and many evidences have been reported on the influence of custom in building Islamic rulings. This is clearly that indicates its status and position in Islamic law, and custom is considered an argument and a ruling, when it does not contradict a legal text in many areas. Moreover, the method followed in this article is the descriptive analytical method with the collection of scientific material from authentic sources and the information network (the Internet). It is good and benefit to the writer and reader of these papers, for who is the best responsible and the best supporter.